After the Strike: Changing the Teacher-Board Relationship - Beatty, Carol; Gandz, Jeffrey (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
This paper describes four strike situations, following which teachers and school boards tried to engineer changes to theirprestrike relationships. The authors analyse these situations and identify some ofthefactors which appeared to distinguish the successes from the fallures.